The effects of crop integration on fertilizer cost and oil palm yield / Fazidah Rosli ... [et al.] - Rosli, Fazidah; Wan Romlee, Wan Muhammad Izwan; Hamzah, Nur Masriyah; T Abu Bakar, Tengku Halimatun Sa'adiah (Universiti Teknologi MARA Cawangan Pahang, 2020)
Oil palm crop integration is an effective practice to be applied by oil palm growers in their plantation. The objectives of the study were to determine the effects of crop integration on the cost of fertilizer and to identify the effect of crop integration to the yield of oil palm. The study was carried out at Felda Kota Gelanggi 1, Felda Kota Gelanggi 2, Felda Kota Gelanggi 3, and Felda Kota Gelanggi 4, Pahang. The questionnaire consists of 35 questions that are related to crop integration of oil palm, which are distributed among the respondents. Accordingly, statistical tests that were conducted had included Pearson correlation, Bivariate Correlation, Partial Correlation and Wilcoxon Signed Rank Test. The results indicated that there were differences on the cost of fertilizer before and after crop integration where the P-value is 0.029, and the strength of the correlation is 0.562. They also showed the differences in the amount of oil palm yield where the P-value is 0.006 and that there was a significance results between the oil palm yields before and after crop integration. This study is important to encourage the settlers to apply crop integration and to help them to increase the income and reduce the farm cost. Therefore, the settlers are encouraged to apply crop integration on their oil palm due to the positive results that has been shown.